Green-synthesized metal nanoparticles: a promising approach for accelerated wound healing - Singaravelu, Sivakumar; Motsoene, Fezile; Abrahamse, Heidi; Dhilip Kumar, Sathish Sundar (Frontiers in Bioengineering and Biotechnology, 2025)
The green synthesis of metal nanoparticles (G-MNPs) in wound healing has shown a promising approach in recent decades. While chemical and physical methods have traditionally been employed for G-MNP synthesis, green synthesis methods are increasingly preferred due to their eco-friendly, safe, cost-effective, and efficient nature. These processes offer high productivity and purity without the need for high pressure, temperature, or toxic and hazardous substances, and they eliminate the need for external reducing, stabilizing, or capping agents. The green synthesis of G-MNPs can occur intra- or extracellularly and can be facilitated by various biological entities, including bacteria, fungi, yeast, algae, actinomycetes, and plant extracts. The rapid advancements in nanotechnology have been significantly propelled by the development of engineered, green-synthesized metal nanoparticles (G-MNPs). These nanoparticles have been extensively investigated for their potential applications in various biomedical fields. Their inert nature and nanoscale dimensions, which are comparable to many biological molecules, make them highly attractive in the biomedical field. Moreover, their intrinsic properties, including electronic, optical, physicochemical characteristics, and surface plasmon resonance, are highly tunable by altering parameters such as particle size, shape, environment, aspect ratio, synthesis methods, and functionalization. This tunability has facilitated their broad application in biomedicine, encompassing areas such as targeted drug delivery, biosensing, photothermal and photodynamic therapies, imaging, and the integration of multiple therapeutic modalities. This review article explores the various properties of metallic nanoparticles and their applications in the biomedical sciences while also addressing the challenges associated with their clinical translation.